Wschodniosłowiańskie i polskie pieśni tradycyjne jako uniwersalny nośnik kultury - Braszak, Piotr (Scripta Neophilologica Posnaniensia, 2020)
In the presented article, the author considers a rarely discussed subject of traditional song lyrics perceived as culture transmitters. Even though they are very universal and comprehensive sources in terms of cultural transmission, academics use them in scientific discourse incommensurately less frequently than other textual forms or art works from the epoch. The author analyzes traditional folk songs as texts which unfold before the reader. Their crucial value and broad possibility to understand different and interfusing realms of human activity associated with Polish and East Slavic culture are presented.